(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The presence of harmful compounds like caffeine and carbonated compounds in different beverages like soft drinks, fruit juices deserves great attention because of its toxic and carcinogenic effects on human beings. We report on the detection and purification of those substances with the help of HPLC(High Performance Liquid Chromatography).According to the migration rate, stationary phase and mobile phase, retention time we can extract the desire compounds. Depending upon the solvent and sample we can detect the compounds with the help of the detector.The chromatogram will be displayed and it can be viewed in the PC with the help of Osiris software. Compounds like Caffeine, Aspartame, Neotame, Saccharin, Maltodextrin, sucrose, fructose etc can be detected and purified. Detection and purification takes place in the column of HPLC where the process called adsorption takes place. Retention time can be calculated by the total time taken of a component that spends in both mobile phase and stationary phase. It is always expressed in minutes